2008 47th IEEE Conference on Decision and Control 2008
DOI: 10.1109/cdc.2008.4739313
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive output tracking control of a surface vessel

Abstract: Abstract-In this paper, the tracking control of a three degree-of-freedom marine vessel is examined. The novelty of this work is the transformation of the asymmetric inertia matrix into a symmetric, positive definite matrix. The asymmetry arises from the added mass common to practical surface vessels and creates a significant challenge for control design. The control design is further complicated by the parametric uncertainties in the dynamic model of the vessel. Two adaptive control schemes with a projection-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Here, our aim is to show the efficacy of the proposed control approach compared with the previous output feedback control system in [24]. It is shown that, their proposed output feedback controller shows a satisfactory tracking performance in the presence of parametric uncertainties.…”
Section: Comparative Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Here, our aim is to show the efficacy of the proposed control approach compared with the previous output feedback control system in [24]. It is shown that, their proposed output feedback controller shows a satisfactory tracking performance in the presence of parametric uncertainties.…”
Section: Comparative Studymentioning
confidence: 99%
“…Also, the parametric uncertainties and model uncertainties are ignored in this work. By transforming the inertia matrix into a symmetric form, two adaptive controllers (a full-state feedback controller and an output feedback controller) in the presence of parametric uncertainties are proposed in [24]. However, non-parametric uncertainties are ignored in the design of the controller.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [11], based on the transformation of open loop tracking error into a skewsymmetric form, a continues, time-varing control law was proposed, but disrurbances were not consider in the model of the system. Two adaptive control schemes were proposed in [12]. Both controllers were known to yield uniformly ultimately bounded tracking result and environmental disturbances were not consider in this work.…”
Section: Introductionmentioning
confidence: 98%
“…However, it is extremely challenging to obtain an accurate model that will satisfactorily capture the dynamic behavior of the system. Fortunately, adaptive control strategies present a reasonable solution to overcome parametric uncertainties [11][12][13]. In [11], based on the transformation of open loop tracking error into a skewsymmetric form, a continues, time-varing control law was proposed, but disrurbances were not consider in the model of the system.…”
Section: Introductionmentioning
confidence: 99%